PENGARUH LINGKUNGAN KERJA DAN DISIPLIN TERHADAP KINERJA KARYAWAN PT. SSI SEASONAL SUPPLIES INDONESIA AREA CIKUPA DIVISI PRODUKSI - Eka Nanda Putra, Pradana; Ratnasih, Pancagaluh (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of the work environment and discipline on employee performance at PT. SSI Seasonal Supplies Indonesia Cikupa Area Production Division, both partially and simultaneously. The method used is a quantitative method. The sampling technique used was saturated sampling using a sample of 56 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis tests. The results of this research are that the work environment has a significant effect on employee performance based on hypothesis testing obtained with Tcount > Ttable (11,586 > 1.674), the value of ρ < Sig.0.05 or (0.000 < 0.05) which means that H0 is rejected and H1 is accepted and The regression equation value obtained is Y = 11.586 and The determination or contribution value is 0.359 or 35.9%. Work discipline has a significant effect on employee performance based on the hypothesis test obtained with the value Tcount > Ttable (6,444 > 1.674), the value ρ < Sig. 0.05 or (0.000 < 0.05) which means H0 is rejected and H2 is accepted and the value obtained regression equation Y = 6.444 and X2 0.674, the correlation coefficient value is 0.772, meaning that the two variables have a strong positive relationship. The value of determination or contribution of influence is 0.589 or 58.9%. Work environment and work discipline simultaneously have a significant effect on employee performance based on hypothesis testing obtained with a value of Fcount > Ftable or (41,690 > 3.17) value of ρ < Sig.0.05 or (0.000 < 0.05) which means H0 is rejected and H3 is accepted and the regression equation value Y = 6.922, X1 = -0.212, X2 = 0.861 is obtained. The correlation coefficient value or the level of relationship between the independent variable and the dependent variable is 0.782, meaning it has a positive level of relationship with a perfect degree of correlation. The determination or contribution value is 0.597 or 59.7%